2017
DOI: 10.4184/asj.2017.11.5.686
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering RNA–Mediated Suppression of Fas Modulate Apoptosis and Proliferation in Rat Intervertebral Disc Cells

Abstract: Study DesignIn vitro cell culture model.PurposeTo investigate the effect of small interfering RNA (siRNA) on Fas expression, apoptosis, and proliferation in serum-deprived rat disc cells.Overview of LiteratureSynthetic siRNA can trigger an RNA interference (RNAi) response in mammalian cells and precipitate the inhibition of specific gene expression. However, the potential utility of siRNA technology in downregulation of specific genes associated with disc cell apoptosis remains unclear.MethodsRat disc cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…B. Park and C. Park [ 38 ] found that Fas siRNA might be a powerful therapeutic approach for disc degeneration by suppression of harmful gene expression. The characteristic of IDD is that the dysfunctional FASL reduce the expression level of FASL and unbalance the interaction between NP cells and immune cells, leading to the expression of certain regulatory factors that may play a role in this process [ 33 ], such as hsa_circ_0001658 and hsa-miR-181c-5p in this study.…”
Section: Discussionmentioning
confidence: 99%
“…B. Park and C. Park [ 38 ] found that Fas siRNA might be a powerful therapeutic approach for disc degeneration by suppression of harmful gene expression. The characteristic of IDD is that the dysfunctional FASL reduce the expression level of FASL and unbalance the interaction between NP cells and immune cells, leading to the expression of certain regulatory factors that may play a role in this process [ 33 ], such as hsa_circ_0001658 and hsa-miR-181c-5p in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR experimental method used in this study was the same as described in a previous paper [ 10 ]. Briefly, total RNA was extracted from NP cells and tissues using TRIzol regent (Invitrogen, Grand Island, NY, USA) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In the early stage of apoptosis, Fas downregulation can reduce apoptosis and induce proliferation, resulting in enhanced IVD cell viability. Fas siRNA may be an effective method for treating IDD 84 . In addition, it has been reported that RNA interference is a promising method of local IDD therapy 85 .…”
Section: The Death Receptor Pathway and Iddmentioning
confidence: 99%